A Model of User Satisfaction and Quality in The Implementation ‎of SISKEUDES - Supraja, Galih; Erlina; Atmanegara, Agung Wahyudhi; Erwin, Keulana; Kumalasari, Fauziah (International Journal of Accounting and Economics Studies, 2026)
This study aims to analyze the extent to which system quality and information quality influence users’ perceived usefulness and user satisfaction with the SISKEUDES system. An explanatory quantitative approach was employed, using Structural Equation Modeling–Partial ‎Least Squares (SEM-PLS) as the analytical technique. The study population consisted of village officials who use SISKEUDES in regency-level governments across North Sumatra Province, with a sample of 303 respondents. Data were collected through questionnaires distributed via Google Forms and analyzed using SmartPLS version 4. The results indicate that both system quality and information quality have a positive and significant effect on perceived usefulness and user satisfaction. Furthermore, perceived usefulness significantly influences user ‎satisfaction and acts as a partial mediating variable in the relationship between system quality, information quality, and user satisfaction. ‎These findings are consistent with the Technology Acceptance Model (TAM), which emphasizes that information system effectiveness is ‎shaped by technical system quality, the quality of information produced, and users’ perceptions of system usefulness. The findings of this ‎study are expected to provide a foundation for policy formulation and for improving both system performance and information quality in the ‎future development of SISKEUDES.
Keywords: User Approval or Satisfaction Model; Quality System; Quality Information; Perceived Value of Use; SISKEUDES